Amyloid burden, cerebrovascular disease, brain atrophy, and cognition in cognitively impaired patients. Issue 5 (18th July 2014) - Ye, Byoung Seok; Seo, Sang Won; Kim, Geon Ha; Noh, Young; Cho, Hanna; Yoon, Cindy W.; Kim, Hee Jin; Chin, Juhee; Jeon, Seun; Lee, Jong Min; Seong, Joon-Kyung; Kim, Jae Seung; et al.
Abstract: Background: We investigated the independent effects of Alzheimer's disease (AD) and cerebrovascular disease (CVD) pathologies on brain structural changes and cognition. Methods: Amyloid burden (Pittsburgh compound B [PiB] retention ratio), CVD markers (volume of white matter hyperintensities [WMH] and number of lacunae), and structural changes (cortical thickness and hippocampal shape) were measured in 251 cognitively impaired patients. Path analyses were utilized to assess the effects of these markers on cognition. Results: PiB retention ratio was associated with hippocampal atrophy, which was associated with memory impairment. WMH were associated with frontal thinning, which was associated with executive and memory dysfunctions. PiB retention ratio and lacunae were also associated with memory and executive dysfunction without the mediation of hippocampal or frontal atrophy. Conclusions: Our results suggest that the impacts of AD and CVD pathologies on cognition are mediated by specific brain regions.